Subcutaneous multiplication of exfoliatin-producing staphylococci. - Kapral, F A (1976)
After subcutaneous inoculation of approximately 10(6) cocci, changes in staphylococcal populations were followed by the enumeration of organisms in excised tissues. In contrast to conventionaal Staphylococcus aureus strains, exfoliatin-producing strains were able to multiply in the subcutaneous tissues of neonatal and adult mice. Although strains capable of producing large quantities of exfoliatin were better able to proliferate than strains producing lesser amounts of toxin, it was not determined whether exfoliatin was directly responsible for the observed multiplication. Two variants exhibiting a partial loss in exfoliatin production showed minor changes in proliferative capability. A third strain, after being cured of its exfoliatin plasmid, manifested a marked reduction in exfoliatin production and was unable to multiply subcutaneously. With some strains multiplication proceeded for several hours but was then followed by a decline in the number of viable organisms. Histological sections of subcutaneous lesions revealed a rapid influx of neutrophils, but leukocytes accumulated in the region regardless of whether the organisms multiplied or were eliminated.